Analysis of Factors Affecting the Performance of Nurses in the Internal Room of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City - M. Haikal Wahyudin; Sabirin B. Syukur; Muriyati Rokani (Universitas Muhammadiyah Palu, 2026)
Nurse performance is a measure of success in achieving nursing service goals. The performance of nurses in providing nursing care is influenced by several factors such as education, work motivation and job satisfaction. This study aims to analyze the Factors Affecting the Performance of Nurses in the Internal Room of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City. The quantitative method with the research design used in the study was quantitative with correlational analytics with a cross sectional design. This is a cross sectional, where the sample is selected through the total sampling method, with a sample of 35 nurse respondents in the Internal Room The sample in this study is all nurses in the Internal Room of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City. Data analysis used the chi square test (x2) with a meaning (< 0.05). The results of the study showed that there was a relationship between the last education of nurses (p.0.019), work motivation (p. 0.021) and Nurse Job Satisfaction (p. 0.015) with Nurse Performance in the Internal Room of Prof. Dr. H. Aloei Saboe Hospital Gorontalo City is evidenced by a p-value (?0.05), The suggestion in this study is the need for periodic evaluation related to the performance of nurses in improving the quality and quality of nursing services in the Internal Room.